2010
DOI: 10.1007/s00425-010-1165-2
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and abscisic acid signaling orthologs are activated at the onset of ripening in grape

Abstract: The onset of ripening involves changes in sugar metabolism, softening, and color development. Most understanding of this process arises from work in climacteric fruits where the control of ripening is predominately by ethylene. However, many fruits such as grape are nonclimacteric, where the onset of ripening results from the integration of multiple hormone signals including sugars and abscisic acid (ABA). In this study, we identified ten orthologous gene families in Vitis vinifera containing components of sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 83 publications
(120 reference statements)
8
137
1
Order By: Relevance
“…In studies by my research group, however, the expression patterns of VlMYBA1-2, VlMYBA1-3, and VlMYBA2 did not resemble the pattern of endogenous ABA levels (Azuma et al, 2012b). This suggests that the final anthocyanin content and the expression levels of related genes under natural conditions are determined by complex interactions among internal and external factors such as temperature, light, water status, sugar content, and endogenous ABA content Gambetta et al, 2010;Hiratsuka et al, 2001;Jeong et al, 2004;Kataoka et al, 1984Kataoka et al, , 2003Kliewer and Torres, 1972;Matus et al, 2009;Mori et al, 2007;Yamane et al, 2006). It also suggests that artificial ABA treatment can enhance the expression of MYB genes and of genes in the anthocyanin biosynthesis pathway.…”
Section: Aba Content and Expression Pattern Of Nced1mentioning
confidence: 84%
“…In studies by my research group, however, the expression patterns of VlMYBA1-2, VlMYBA1-3, and VlMYBA2 did not resemble the pattern of endogenous ABA levels (Azuma et al, 2012b). This suggests that the final anthocyanin content and the expression levels of related genes under natural conditions are determined by complex interactions among internal and external factors such as temperature, light, water status, sugar content, and endogenous ABA content Gambetta et al, 2010;Hiratsuka et al, 2001;Jeong et al, 2004;Kataoka et al, 1984Kataoka et al, , 2003Kliewer and Torres, 1972;Matus et al, 2009;Mori et al, 2007;Yamane et al, 2006). It also suggests that artificial ABA treatment can enhance the expression of MYB genes and of genes in the anthocyanin biosynthesis pathway.…”
Section: Aba Content and Expression Pattern Of Nced1mentioning
confidence: 84%
“…In berries, the onset of ripening (veraison) when anthocyanin accumulation begins in red varieties, is accompanied by a marked increase in ABA concentration (Deluc et al, 2009;Gambetta et al, 2010) and correlates well with sugar accumulation (Gambetta et al, 2010). ABA has been shown to activate anthocyanin biosynthetic genes and the anthocyanin-synthesis related VvmybA1 transcription factor (Jeong et al, 2004), and to induce the delay of expression of proanthocyanidin biosynthetic genes (VvANR and VvLAR2) (Lacampagne et al, 2009).…”
Section: Abscisic Acidmentioning
confidence: 99%
“…Several studies have underlined the role of ABA in enhancing softening in both tomato (Zhang et al, 2009b) and grapevine (Gambetta et al, 2010). Indeed, it was suggested by Koyama et al (2010) that in grape berry, the modification of cell walls occurring under ABA treatment may be reflected by the differential transcript abundances of cell wall proteins and pectin-modifying enzymes.…”
Section: Effects On Ripening-associated Processesmentioning
confidence: 99%
“…ABA content of grape berries gradually and strongly increases just before the onset of ripening, called véraison (Coombe and Hale, 1973;Scienza et al, 1978;Davies et al, 1997;Antolín et al, 2003;Deluc et al, 2009). In relation with its accumulation profile, numerous reports suggested that ABA may play a major role in controlling several ripening-associated processes of grape berry, including coloration, sugar accumulation, and softening (Coombe, 1992;Davies et al, 1997;Giovannoni, 2001; Rodrigo et al, 2003;Yu et al, 2006;Wheeler et al, 2009;Gambetta et al, 2010;Giribaldi et al, 2010;Gagné et al, 2011).…”
mentioning
confidence: 99%